PENGARUH DUKUNGAN MANAJEMEN PUNCAK TERHADAP KUALITAS SISTEM INFORMASI AKUNTANSI PADA PERUSAHAAN ASURANSI SYARIAH - Cahyadi, Wahyu; Mukhlisin, Murniati; Pramono, Sigid Eko (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
This study is objected to test the support of top managementÂ  that can enhance the quality of Accounting Information Systems (SIA) in Islamic insurance companies in Indonesia. This study uses qualitative methods with a positive paradigm. The data used are primary data with the help of questionnaires as research instruments. Data obtained from returning questionnaires filled out by respondents who are leaders, division heads, department heads or heads of accounting departments. The research population is a sharia insurance company consisting of 59 companies registered as members of the Indonesian Sharia Insurance Association (AASI) as of April 2019. From the population obtained 34 respondents who filled out the questionnaire. Data analysis was performed with descriptive static and PLS-structural equation modelling (PLS-SEM) using SmartPLS software. The results showed that top management's support had a significant effect on the quality of accounting information systems and support of top management has not been maximized.